Resolution Improvement for Coherent Illumination Microscopy via Incident Light Phase Modulation - Jinzhong Ling; Yangyang Li; Jinkun Guo; Xin Liu; Xiaorui Wang (Optics)
In order to break the diffraction limit and improve the imaging resolution of optical microscope, in this article, we theoretically deduced the influence of phase difference on imaging resolution under coherent illumination. As the phase difference increased, the resolution improved gradually. Inspired by this conclusion, a super-resolution optical imaging system based on phase modulation was proposed and simulated. An optical mask was designed to generate additional phase difference for the adjacent area at the sample’s surface, and the influence of its structural parameters was analyzed numerically. The simulation results preliminarily confirm the feasibility of this scheme, laying the foundation for a more optimal and comprehensive super-resolution imaging scheme. Due to its advantages of high resolution, a wide field of view, and being compatible, this non-fluorescence super-resolution imaging scheme is worthy of further research and application.